2010
DOI: 10.1007/s11136-010-9780-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children with mitral valve prolapse

Abstract: ObjectiveThe aim of our prospective study was to assess the health-related quality of life (HRQOL) of children with mitral valve prolapse (MVP) and the impact of clinical symptoms on HRQOL.MethodsSixty-seven patients with primary MVP aged 8–18 years were studied and compared with 31 healthy children. All children completed the polish version of KIDSCREEN-27. For searching occurrence and frequency of 18 clinical symptoms, authors’ questionnaire was used.ResultsThe statistically significant difference was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
5
0
4
Order By: Relevance
“…However, one can ascertain that a large part of the studies performed is at a lower level of HRQoL among children and adolescents with CHD when compared to healthy control 35 - 37 . According the findings of a systematic review conducted by Dahan-Oliel, Majnemer and Mazer 38 , such results are related in part to the physical limitations - actual or perceived - in subjects with CHD, which can lead to unnecessary restrictions and overprotective behavior that possibly interfere in their perception over QoL.…”
Section: Review Results and Discussionmentioning
confidence: 99%
“…However, one can ascertain that a large part of the studies performed is at a lower level of HRQoL among children and adolescents with CHD when compared to healthy control 35 - 37 . According the findings of a systematic review conducted by Dahan-Oliel, Majnemer and Mazer 38 , such results are related in part to the physical limitations - actual or perceived - in subjects with CHD, which can lead to unnecessary restrictions and overprotective behavior that possibly interfere in their perception over QoL.…”
Section: Review Results and Discussionmentioning
confidence: 99%
“…Las chicas perciben peor CVRS tanto en aspectos físicos como emocionales. Este hecho ha sido explicado por diferentes razonamientos, por un lado, en ellas los cambios físicos son más drásticos y la menstruación y las fluctuaciones hormonales propician peor bienestar físico 6 . Por otro lado, las chicas son más reflexivas y conscientes de sí mismas y culturalmente es más aceptable que verbalicen más sus problemas 19 , presentan más síntomas psicosomáticos, más estrés e inseguridad 1 .…”
Section: Discussionunclassified
“…Desde esta perspectiva los síntomas psicosomáticos pueden ser considerados como manifestaciones de malestar emocional 5 y estrés psicológico 2 , y pueden interferir en la percepción de la calidad de vida relacionada con la salud (CVRS). La incorporación del KIDSCREEN como instrumento específico para medir la percepción de la CVRS en niños y adolescentes ha permitido el desarrollo de numerosos estudios de investigación en población enferma6, 7 y sana 8 . Al ser un instrumento multidimensional explora múltiples facetas importantes en esta edad.…”
Section: Introductionunclassified
“…Current research on the evaluation of healthrelated quality of life in children and adolescents with congenital heart disease has presented conflicting results, possibly owing to the lack of methodological and conceptual rigour. 6 However, it is possible to affirm that a major part of these studies have found a lower level of health-related quality of life among children and adolescents with congenital heart disease when compared with healthy controls, [7][8][9][10][11][12] in dimensions such as Physical Well-Being, 7 autonomy, motor functioning and social and emotional functioning, 10 depressive symptoms, and psychological adjustment. 13,14 In contrast, other studies have shown that adolescents with congenital heart disease have an equal or higher health-related quality of life than healthy norms, [15][16][17] especially when they have a good social support network and parental support.…”
Section: A Dvances In Cardiac Surgery and Earlymentioning
confidence: 99%